2010
DOI: 10.1088/0067-0049/192/1/5
|View full text |Cite
|
Sign up to set email alerts
|

The Hetdex Pilot Survey. I. Survey Design, Performance, and Catalog of Emission-Line Galaxies

Abstract: We present a catalog of emission-line galaxies selected solely by their emission-line fluxes using a wide-field integral field spectrograph. This work is partially motivated as a pilot survey for the upcoming Hobby-Eberly Telescope Dark Energy Experiment. We describe the observations, reductions, detections, redshift classifications, line fluxes, and counterpart information for 397 emission-line galaxies detected over 169 with a 3500-5800 Å bandpass under 5 Å full-width-half-maximum (FWHM) spectral resolution.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
147
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 121 publications
(135 reference statements)
0
147
1
Order By: Relevance
“…A complete description of this pathfinding survey and its data products is given in Adams et al (2011). Briefly, a square 246-fiber array was mounted on the Harlan J. Smith 2.7 m telescope at McDonald Observatory and coupled to the George and Cynthia Mitchell Spectrograph, a proto-type of the Visible Integral-field Replicable Unit Spectrograph (VIRUS) designed for HETDEX (Hill et al 2008b).…”
Section: The Hetdex Pilot Survey Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A complete description of this pathfinding survey and its data products is given in Adams et al (2011). Briefly, a square 246-fiber array was mounted on the Harlan J. Smith 2.7 m telescope at McDonald Observatory and coupled to the George and Cynthia Mitchell Spectrograph, a proto-type of the Visible Integral-field Replicable Unit Spectrograph (VIRUS) designed for HETDEX (Hill et al 2008b).…”
Section: The Hetdex Pilot Survey Datamentioning
confidence: 99%
“…In Adams et al (2011), X-ray counterparts were identified for 30 of the HETDEX pilot survey's [O ii] emitters. However, many of these objects are in the GOODS-N region, where the Chandra images are deep enough to detect the X-rays associated with normal star formation (e.g., Persic et al 2004;Lehmer et al 2010).…”
Section: The Hetdex Pilot Survey Datamentioning
confidence: 99%
“…Rhoads et al 2000;Ouchi et al 2008;Ciardullo et al 2012), long-slit spectroscopy (Rauch et al 2008;Cassata et al 2011) or integral field spectroscopy (e.g. Petitjean et al 1996;Adams et al 2011). Because their selection is independent of the stellar continuum, these galaxies are often faint in broad-band imaging and likely represent lowmass systems with little dust attenuation (Gawiser et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Galaxies detected by their strong Lyman-α (Lyα) emission, called Lyα emitters (LAEs), have become an important tool in understanding cosmology at intermediate-to-high redshifts (z > 1.5), such as for the large-scale matter distribution (Hill et al 2008;Adams et al 2011) or the epoch of reionization via the connection of LAEs and Lyman-continuum leakers (Behrens et al 2014;Verhamme et al 2014;Dijkstra 2014). The physical type(s) of objects classified as LAEs and the connection of the observed line profiles to the physical properties of the emitters are still a matter of debate, though progress has been made in recent years (e.g., Ahn et al 2003;Verhamme et al 2006;Dijkstra & White 2010).…”
Section: Introductionmentioning
confidence: 99%